Keep calm in an emergency: an unexpected case with poisoning - Liu, Guang-Hui (Journal of Thoracic Disease, 2014)
It was 11:40 p.m and I was on the night shift in the emergency room when I received a call from the front desk: “Get ready; a patient with palpitations and sweating is on his way”.